Działalność Zgromadzenia Sióstr Służebniczek Najświętszej Maryi Panny Niepokalanie Poczętej jako realizacja misyjnego posłannictwa Kościoła - Machalski, Jędrzej (Annales Missiologici Posnanienses, 2020)
Since the apostolic times, the Church has continuously fulfilled the invitation addressed by Jesus to his disciples: Go ye into all the world, and preach the Gospel to every creature (Mark 16:15). The Second Vatican Council, writing about the missionary nature of the Church, clearly emphasized the importance of the task of bringing the Good News to all people on Earth. This mission includes the activity of the Sisters Servants of the Holy and Immaculate Virgin Mary, a congregation founded by blessed Edmund Bojanowski. Although the congregation was not established with missionary work in mind, the first Sisters left Poland as early as 1928, realizing the deep missionary awareness that had always been present in Bojanowski. Currently, the Sisters work almost on all continents, running schools and nurseries for children, serving the sick in clinics and hospitals, working for charity, parishes and pastoral care. The spring months faced the Sisters with the challenge of dealing with the covid-19 virus epidemic, which affected, among others, the functioning of the hospitals and schools run by the Sisters, putting many children in poor health at risk because of the conditions in which they live. The Sisters often added a request for prayer and support to the current news published on the Internet. Although due to the epidemic, the departures of volunteers became impossible, many people of good will supported and continue to support the missionary activity of the Sisters, remembering the words of Christ: Truly I say to you, to the extent that you did it to one of these brothers of Mine, even the least of them, you did it to Me (Matthew 25:40).